(untitled) (International Journal of Environmental Sciences, 2025)
Introduction:Antimicrobial resistance (AMR) is an important public health threat, which has become increasingly complex due to a host of hospital-based factors including misuse of antibiotics, inadequate infection control, and patient transfer between hospitals. Knowledge of these drivers is necessary to develop interventions. The purposes of this systematic review are to describe principal hospital-related AMR drivers, to evaluate AMS and infection control interventions, and to proffer guidelines that can be used to pre-empt AMR. Methodology:We searched PubMed, Embase, Scopus, and the Cochrane Library systematically for studies from March 2015 until March 2025. Eligibility criteria and sources of information All original studies on hospital-related risk factors and interventions on AMR were included, while review and qualitative studies were excluded. Two reviewers independently conducted data extraction and ‘risk of bias’ (RoB) assessment using standardised tools (e.g. NOS, EPOC). Pooled effects were estimated using a random-effects model for the meta-analysis. Results:There were ten studies from different geographical areas. Commonly identified risk factors were: catheterization, previous antibiotic medication, underlying diseases, and routes of patient transfer. AMS measures also resulted in decreased antibiotic consumption (24.3% decrease in DOT in one study) and better resistance patterns. Meta-analysis demonstrated a pooled odds ratio of 0.91 (95% CI: 0.75–1.12), suggesting a favorable trend towards lower AMR with hospital interventions. There was low to moderate risk of bias in the studies. Conclusion:Hospital practices have a significant impact on the emergence and spread of AMR. Evidence supports the implementation of AMS programs, infection control protocols, and molecular surveillance as effective strategies for AMR containment. Strengthening these practices, especially in resource-limited settings, is critical to reducing the global AMR burden.